Attitudes and intentions towards mental health assistance by New Zealand's baby boomers : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Albany, New Zealand - Macfarlane, Joanna (Massey University, 2015)
Little information exists regarding baby boomers‘ attitudes and intentions towards mental health help-seeking. This is surprising considering this generation, known for its size and living through the most influential period of social change in history, is associated with increased rates of certain mental health disorders. As this cohort age over 65, information about intentions or attitudes towards help-seeking for increasingly common disorders in older age (depression, anxiety, the dementias and substance abuse) is crucial. This research examined this subject by: investigating any intention or attitude differences relating to age; examining intention towards professional and preventive help for the four mental health concerns outlined above; and determining the association between and contribution of relevant variables towards the baby boomers‘ stated help-seeking intentions within the framework of a social cognitive model of help-seeking: the Theory of Planned Behaviour (TPB). Participants were a convenience sample of 256 New Zealand baby boomers (aged 49-69), who completed an anonymous, self-report questionnaire measuring demographic variables, intention towards professional and preventive help for four disorders, attitudes towards help-seeking, emotional distress and a previous professional help rating. Attitudes towards seeking psychological help and intentions towards seeking professional and preventive help showed no significant differences with relation to age. The cohort were generally positive about seeking both preventive and professional help, and attitude towards seeking help for mental health problems was also positive. Intention towards professional help was higher for depression and substance abuse than for anxiety and forgetfulness (the dementias). For preventive help, intentions were uniformly high across all four disorders. Within the TPB model, support was achieved for the TPB variables Psychological Openness (PO) and to an extent Perceived Behavioural Control (PBC) as significant predictors of professional help-seeking behaviour and their contribution in explaining help-seeking behaviour in this cohort. PO and PBC associated significantly with professional and preventive intent across most disorders investigated. The implications of these findings and directions for future research are discussed.
Keywords: Baby-boomers, New Zealand; Middle-aged people, New Zealand; Older people, New Zealand; Baby-boomers' mental health; Mental health services